2004
DOI: 10.1111/j.1471-0528.2004.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence: prevalence and association with gynaecological symptoms

Abstract: Objective To determine the prevalence of domestic violence in a population of women attending a gynaecology outpatient clinic in the United Kingdom and also to investigate whether women who reported domestic violence were more likely to complain of certain gynaecological symptoms. Design Questionnaire survey.Setting A gynaecology outpatient clinic in a North of England Hospital.Sample Nine hundred and twenty consecutive clinic attenders.Methods Anonymous confidential questionnaire given to women.Main outcome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 28 publications
5
48
1
1
Order By: Relevance
“…Studies have shown that a history of childhood sexual abuse ranges from 15% to 25% [18][19][20]. Multiple studies have examined the prevalence of physical abuse among women with ranges from 5% to 28% [21][22][23][24][25]. When comparing the above prevalence rates with those found among the IC sample, both depression and a history of sexual abuse were found to be statistically significant (P<0.05) (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Studies have shown that a history of childhood sexual abuse ranges from 15% to 25% [18][19][20]. Multiple studies have examined the prevalence of physical abuse among women with ranges from 5% to 28% [21][22][23][24][25]. When comparing the above prevalence rates with those found among the IC sample, both depression and a history of sexual abuse were found to be statistically significant (P<0.05) (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Scores range from 0 to 63 with higher scores representing more severe symptoms. Scores can be further stratified into categories of depression: mild depression (14)(15)(16)(17)(18)(19), moderate depression (20)(21)(22)(23)(24)(25)(26)(27)(28), and severe depression . A score of less than 14 is considered normal.…”
Section: Measurement Of Depressionmentioning
confidence: 99%
“…The prevalence of physical violence is higher in the last mentioned countries than others. The prevalence of physical violence at workplace in our country and other countries have been reported between 16-36% [36][37][38][39][40][41], it is due to variation in populations study, and also because of different type of study, different cultures, and different social and economic context. In the present study, physical violence has taken first place in most of reviewed studies.…”
Section: Discussionmentioning
confidence: 99%
“…The study, by John and colleagues, 51 reported a 21% lifetime prevalence of physical violence and a 1-year prevalence of 4%, with most abuse being perpetrated by ex-husbands or ex-boyfriends (32% and 29% respectively). Prevalence was highest in women aged 31-40 years.…”
Section: Gynaecology Clinicsmentioning
confidence: 99%